A lithium-copper-titanium co-doped p2-type layered oxide positive electrode material and a preparation method thereof
Patent Information
- Application Number
- CN202611189948.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]但是,现有技术中各取代元素通常分别针对某一性能进行调节,材料容量、宽电压结构稳定性和高倍率循环性能之间仍存在相互制约
本发明通过在P2型锰基层状氧化物中按照限定的化学计量关系同时引入Li、Cu和Ti,使所得锂铜钛共掺杂P2型层状氧化物正极材料在保持P2相层状主体结构的同时形成超晶格结构,优选形成蜂窝状超晶格有序结构,从而使特定元素组成与晶体有序结构相互配合,改善宽电压充放电过程中可逆容量、倍率性能和循环稳定性难以兼顾的问题。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery electrode materials technology, and more specifically, to a lithium copper-titanium co-doped P2-type layered oxide cathode material and its preparation method. Background Technology
[0002] Sodium-ion batteries have potential applications in large-scale energy storage and low-to-medium speed power applications due to the abundance and low cost of sodium resources and the high compatibility of their manufacturing process with existing lithium-ion battery manufacturing systems. Layered transition metal oxides possess high theoretical specific capacity and fast sodium-ion diffusion channels, making them an important technological route for sodium-ion battery cathode materials. Among them, P2-type manganese-based layered oxides offer advantages such as low cost and high reversible capacity.
[0003] However, P2-type manganese-based basal oxides are prone to transition metal redox state changes, transition metal layer slip, irreversible structural phase transitions, and lattice oxygen side reactions during charge-discharge over a wide voltage window. Furthermore, localized lattice distortions related to Mn³⁺ may occur during low-potential insertion / extraction processes. These structural changes lead to increased polarization, capacity decay, and decreased rate performance, limiting their application in high-power and long-life sodium-ion batteries.
[0004] To address these issues, existing technologies have proposed solutions such as elemental substitution, surface coating, particle morphology control, and transition metal ordering. Previous studies have used honeycomb superlattice ordered structures to regulate cation arrangement in transition metal layers, mitigating cation migration during cycling. Other techniques employ multi-element substitutions such as Li / Cu, Cu / Ti, or Li / Ti to improve the structural stability and ion transport performance of layered oxides. Furthermore, there are reports of multi-element substitution of P2 materials to form honeycomb superlattice structures.
[0005] However, in existing technologies, each substitution element is typically adjusted individually for a specific performance characteristic, resulting in mutual constraints between material capacity, wide voltage range structural stability, and high-rate cycling performance. In particular, for Li-Cu-Ti-Mn layered oxide systems without Ni, Co, and Fe, determining the ratio of Li, Cu, and Ti to achieve a stable honeycomb superlattice ordered structure while maintaining the P2 layered main phase, and simultaneously achieving high reversible capacity, high-rate performance, and long-cycle stability within a 2.0–4.5 V voltage window, requires further investigation.
[0006] Therefore, it is necessary to provide a P2-type layered oxide cathode material with a specific composition ratio of Li, Cu, Ti and Mn and a superlattice ordered structure, and to provide a method for stably preparing the material. Summary of the Invention
[0007] To overcome the aforementioned deficiencies of the prior art, this invention provides a lithium copper-titanium co-doped P2-type layered oxide cathode material and its preparation method. By controlling the stoichiometric relationship of Li, Cu, Ti, and Mn, and combining raw material dispersion, complexation, drying followed by ball milling, and two-step calcination, a lithium copper-titanium co-doped cathode material with both P2-phase layered structure and superlattice structure is obtained, thereby solving the problems mentioned in the background art.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A lithium-copper-titanium co-doped P2-type layered oxide cathode material, wherein the general chemical formula of the cathode material is Na. x Li a Cu b Ti c Mn (1 a b c) O2, wherein 0.1≤a≤0.3, 0.1≤b≤0.2, 0.03≤c≤0.08, and a+b+c≤0.4; a, b, c and 1-abc represent the stoichiometric coefficients of Li, Cu, Ti and Mn respectively, and x represents the stoichiometric coefficient of Na; the cathode material has a P2 phase layered structure and a superlattice structure.
[0009] As a further embodiment of the present invention, the superlattice structure is a honeycomb superlattice ordered structure, and the X-ray diffraction pattern of the cathode material has the characteristic diffraction peaks of the honeycomb superlattice ordered structure in the range of 2θ of 20° to 40°.
[0010] A lithium-copper-titanium co-doped P2-type layered oxide cathode material, characterized by x=0.67, a=0.20, b=0.15, c=0.05, and the chemical formula of the cathode material is Na. 0.67 Li 0.20 Cu 0.15 Ti 0.05 Mn 0.60 O2.
[0011] A method for preparing a lithium copper-titanium co-doped P2-type layered oxide cathode material, using a sol-gel method, includes the following steps: Step 1: Weigh out sodium source compound, lithium source compound, copper source compound, titanium source compound and manganese source compound according to the feeding ratio corresponding to the chemical formula of the target cathode material. Add the sodium source compound, lithium source compound, copper source compound, titanium source compound and manganese source compound to deionized water and ultrasonically disperse for 10 min to obtain the raw material dispersion system. Step 2: Dissolve the complexing agent in deionized water to obtain a complexing agent solution. Slowly add the raw material dispersion system obtained in Step 1 to the complexing agent solution and continue stirring to obtain a mixed system. Step 3: Heat and stir the mixture obtained in Step 2 in a water bath at 80-90°C for 5-6 hours to obtain a gel. Place the gel in a drying oven and dry it at 120°C for 12 hours to obtain a dry solid. Step 4: Add the dried solid obtained in Step 3 to a ball mill jar for ball milling. The ball-to-material mass ratio is 10:1, the ball milling speed is 200-400 rpm, and the ball milling time is 2-4 hours to obtain dried powder. Step 5: Place the dried powder obtained in Step 4 into a muffle furnace and perform pre-calcination and high-temperature calcination in air atmosphere. The high-temperature calcination is carried out at a heating rate of 2-5℃ / min to 850-950℃ and held for 12-16 hours. After calcination, the powder is cooled to room temperature in the furnace and then ground and sieved to obtain the cathode material.
[0012] As a further embodiment of the present invention, the sodium source compound is one or more of sodium citrate and sodium acetate; the lithium source compound is one or more of lithium acetate and lithium nitrate; the copper source compound is one or more of copper nitrate and copper acetate; the titanium source compound is one or more of titanium dioxide and tetrabutyl titanate; and the manganese source compound is one or more of manganese acetate and manganese nitrate.
[0013] As a further aspect of the present invention, in step one, the amount of sodium source compound and lithium source compound fed in is 5% to 10% more than the stoichiometric amount corresponding to the chemical formula of the target cathode material.
[0014] As a further aspect of the present invention, in step two, the complexing agent is citric acid or oxalic acid.
[0015] As a further aspect of the present invention, in step four, the grinding jar is a zirconia grinding jar, and the grinding balls used are zirconia balls; in step five, the sieving uses a 200-300 mesh sieve.
[0016] As a further embodiment of the present invention, step four uses zirconia grinding balls with a diameter of 5 mm, a ball milling speed of 350 rpm, and a ball milling time of 3 h; in step five, the pre-calcination is heated to 580°C at a heating rate of 3°C / min and held at that temperature for 2 h, and the high-temperature calcination is heated to 900°C at a heating rate of 5°C / min and held at that temperature for 14 h.
[0017] A sodium-ion battery cathode includes a cathode current collector and a cathode active material layer disposed on the cathode current collector, wherein the cathode active material layer comprises the aforementioned lithium copper titanium co-doped P2-type layered oxide cathode material.
[0018] The technical effects and advantages of this invention regarding a lithium copper-titanium co-doped P2-type layered oxide cathode material and its preparation method are as follows: This invention introduces Li, Cu, and Ti simultaneously into a P2-type manganese-based layered oxide according to a defined stoichiometric relationship, so that the resulting lithium copper-titanium co-doped P2-type layered oxide cathode material maintains the P2 phase layered main structure while forming a superlattice structure, preferably a honeycomb-shaped superlattice ordered structure. This allows the specific elemental composition and the ordered crystal structure to complement each other, thereby improving the problem of difficulty in simultaneously achieving reversible capacity, rate performance, and cycle stability during wide voltage charge and discharge processes.
[0019] The sol-gel, drying followed by ball milling, and two-step calcination process employed in this invention improves the mixing uniformity of the precursor components and promotes the formation of the target phase. Excessive addition of sodium and lithium source compounds compensates for volatilization losses during high-temperature processing, enhancing the controllability of the target composition. The resulting cathode material exhibits better rate adaptability, cycle capacity retention, and Na+ performance compared to undoped and single-element doped materials. The apparent diffusion properties reflect the overall technical effect formed by the combination of specific Li / Cu / Ti / Mn composition ratio, P2 phase layered structure, superlattice structure and preparation process. Attached Figure Description
[0020] Figure 1 The images show scanning electron microscope (SEM) images and elemental distribution diagrams of Na, Mn, O, Cu, and Ti for the lithium copper-titanium co-doped P2-type layered oxide cathode material obtained in Example 1. In the figures, SEM stands for Scanning Electron Microscopy, EDS for Energy Dispersive X-ray Spectroscopy, Na represents sodium, Mn for manganese, O for oxygen, Cu for copper, and Ti for titanium. μm represents micrometers, and 2μm represents 2 micrometers.
[0021] Figure 2 The figures show the X-ray diffraction patterns of the cathode materials obtained in Examples 1-3 and Comparative Examples 1-4. In the figures, Intensity is the diffraction intensity, au is an arbitrary unit, 2 Theta is the diffraction angle 2θ, and degree is in degrees.
[0022] Figure 3 This is a comparison graph showing the rate performance of the cathode materials obtained in Example 1 and Comparative Examples 2-4 within a voltage range of 2.0–4.5 V. In the graph, Capacity represents the specific capacity in mAh·g. ¹ represents milliampere-hours per gram, CycleNumber represents the number of cycles, and C represents the charge / discharge rate.
[0023] Figure 4This is a comparison chart of the rate performance of the cathode materials obtained in Examples 1-3 within a voltage range of 2.0–4.5V. In the chart, Capacity represents the specific capacity in mAh·g. ¹ represents milliampere-hours per gram, Cycle Number represents the number of cycles, and C represents the charge / discharge rate.
[0024] Figure 5 This is a comparison of the cycle performance and coulombic efficiency of the cathode materials obtained in Example 1 and Comparative Example 1 at a voltage range of 2.0–4.5V and a 1C rate. In the figure, Capacity represents the specific capacity in mAh·g. ¹ represents milliampere-hours per gram, Coulombic Efficiency represents coulombic efficiency, % represents percentage, Cycle Number represents the number of cycles, V represents volts, and C represents the charge / discharge rate.
[0025] Figure 6 This is a comparison of the cycle performance and coulombic efficiency of the cathode materials obtained in Example 1 and Comparative Example 1 at a voltage range of 2.0–4.5V and a 5C rate. In the figure, Capacity represents the specific capacity in mAh·g. ¹ represents milliampere-hours per gram, Coulombic Efficiency represents coulombic efficiency, % represents percentage, Cycle Number represents the number of cycles, V represents volts, and C represents the charge / discharge rate.
[0026] Figure 7 This is a comparison of the apparent diffusion coefficients of Na⁺ in the cathode materials obtained in Example 1 and Comparative Example 1. In the figure, logD represents the Na⁺ diffusion coefficient. The commonly used logarithm of the apparent diffusion coefficient D, where D is the number of Na atoms. Apparent diffusion coefficient, cm²·s ¹ represents square centimeters per second, Time represents time, and h represents hours.
[0027] Figure 8 The figures show the charge / discharge voltage-specific capacity curves of the cathode materials obtained in Example 1 and Comparative Example 1 at different rates. In the figures, Voltage represents voltage, V represents volts, and Capacity represents specific capacity (mAh·g). ¹ represents milliampere-hours per gram, and C represents the charge / discharge rate. Detailed Implementation
[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] Unless otherwise stated, the water used is deionized water, and all raw materials used are analytical grade reagents.
[0030] The general chemical formula of the lithium-copper-titanium co-doped P2-type layered oxide cathode material in this embodiment is Na. x Li a Cu b Ti c Mn (1 a b c) O2, where 0.1≤a≤0.3, 0.1≤b≤0.2, 0.03≤c≤0.08, and a+b+c≤0.4; a, b, c and 1 a b c represents the stoichiometric coefficients of Li, Cu, Ti, and Mn, respectively, and x represents the stoichiometric coefficient of Na. The resulting cathode material has a P2 phase layered structure and a superlattice structure; furthermore, the superlattice structure is a honeycomb superlattice ordered structure, and its X-ray diffraction pattern has corresponding characteristic diffraction peaks in the range of 2θ from 20° to 40°.
[0031] During the preparation process, the sodium source compound can be selected from one or more of sodium citrate and sodium acetate; the lithium source compound can be selected from one or more of lithium acetate and lithium nitrate; the copper source compound can be selected from one or more of copper nitrate and copper acetate; the titanium source compound can be selected from one or more of titanium dioxide and tetrabutyl titanate; and the manganese source compound can be selected from one or more of manganese acetate and manganese nitrate. The amount of sodium and lithium source compounds fed in excess is 5% to 10% above the stoichiometry of the target cathode material to compensate for the volatilization loss of Na and Li during high-temperature treatment. Citric acid or oxalic acid is used as the complexing agent. The solid obtained from gel drying is ball-milled using a zirconia ball mill jar and zirconia grinding balls, and the product obtained from calcination is sieved through a 200-300 mesh sieve.
[0032] The following examples use sodium acetate trihydrate, lithium acetate, copper nitrate trihydrate, titanium dioxide, and manganese acetate tetrahydrate as the corresponding element sources. The mass of each raw material is calculated based on the actual hydration state and purity of the reagents and the amount of the target element added.
[0033] Example 1
[0034] This embodiment prepares a chemical formula of Na. 0.67 Li 0.20 Cu 0.15 Ti 0.05 Mn 0.60The resulting P2-type layered oxide cathode material co-doped with O2 in the form of copper and titanium is denoted as NLCTM cathode material.
[0035] With a total amount of Li, Cu, Ti, and Mn of 0.02000 mol, and based on the stoichiometric ratio of Li, Cu, Ti, and Mn of 0.20∶0.15∶0.05∶0.60, the target amounts of Li, Cu, Ti, and Mn are 0.00400 mol, 0.00300 mol, 0.00100 mol, and 0.01200 mol, respectively, and the target amount of Na is 0.01340 mol.
[0036] In this embodiment, both the sodium and lithium source compounds were added in 5% excess according to their corresponding stoichiometric amounts. Therefore, the actual amounts of Na and Li added were 0.01407 mol and 0.00420 mol, respectively. The specific feeding relationships of each raw material are shown in Table 1.
[0037] Table 1. Raw material feeding relationship in Example 1
[0038] The weighed sodium acetate trihydrate, lithium acetate, copper nitrate trihydrate, titanium dioxide, and manganese acetate tetrahydrate were added to 100 mL of deionized water and ultrasonically dispersed for 10 min at room temperature to obtain the raw material dispersion system. Sodium acetate, lithium acetate, copper nitrate, and manganese acetate entered the aqueous phase, while titanium dioxide was dispersed in the aqueous phase as fine solid particles. Therefore, this system is collectively referred to as the raw material dispersion system.
[0039] Take another 6.5g of citric acid monohydrate C H O ·H O was added to 50 mL of deionized water and magnetically stirred for 10 min at room temperature to fully dissolve the citric acid monohydrate, thus obtaining a complexing agent solution. Based on the amount of material added, the amount of citric acid monohydrate was approximately 0.03093 mol, and its molar ratio to the total amount of Li, Cu, Ti, and Mn was approximately 1.55:1.
[0040] Under continuous stirring, the raw material dispersion system was slowly added to the complexing agent solution. During the addition process, the mixture was kept continuously flowing to ensure sufficient contact between the metal components in the aqueous phase and the citric acid, and to reduce the deposition of titanium dioxide particles in localized areas. After all the raw materials had been added, stirring continued until no obvious stratification was observed in the system, thus obtaining a mixed system.
[0041] The resulting mixture was heated and stirred continuously in an 85°C water bath for 5.5 hours. As the water gradually evaporated, the volume of the mixture decreased, the viscosity increased, and a viscous gel without obvious stratification gradually formed. This gelation process kept the Na, Li, Cu, Ti, and Mn sources in a small-scale mixed state before entering the high-temperature solid-phase reaction, which is beneficial for reducing local compositional deviations.
[0042] The obtained gel was transferred to a drying oven and dried at 120°C for 12 hours to obtain a loose, blocky, dried solid. The dried solid was then preliminarily crushed and added to a zirconia ball mill jar. Zirconia grinding balls with a diameter of 5 mm were used, and the ball-to-material mass ratio was controlled at 10:1. The mixture was ball-milled at 350 rpm for 3 hours. After ball milling, the blocky solid formed during the gel drying process was refined, and the precursor components were further mixed to form a more uniform dried powder.
[0043] The obtained dried powder was placed in a muffle furnace and subjected to pre-calcination and high-temperature calcination in air atmosphere. During the pre-calcination stage, the temperature was increased to 580℃ at a rate of 3℃ / min, and held for 2 hours to decompose the organic components in the precursor and induce preliminary reactions in the inorganic components. Subsequently, the temperature was increased to 900℃ at a rate of 5℃ / min and held for 14 hours to allow the powder to fully crystallize and form the target layered phase.
[0044] After high-temperature calcination, heating was stopped, and the product was allowed to cool naturally to room temperature with the furnace. The cooled calcined product was then removed, ground, and sieved through a 250-mesh sieve to obtain the NLCTM cathode material.
[0045] In this embodiment, the raw materials are dispersed in an aqueous phase, a citric acid complex is synthesized into a gel, dried, ball-milled, and calcined in two steps to achieve uniform mixing, precursor decomposition, and high-temperature crystallization of a specific ratio of Li, Cu, Ti, and Mn components. The stoichiometric coefficients of Li, Cu, and Ti are 0.20, 0.15, and 0.05, respectively, with a total stoichiometric coefficient of 0.40, and the stoichiometric coefficient of Mn is 0.60.
[0046] The microstructure of the obtained NLCTM cathode material was observed using scanning electron microscopy, and the elemental distribution was measured using energy-dispersive X-ray spectroscopy. Figure 1 As shown, the obtained material consists of multiple primary particles aggregated to form micron-scale secondary particles. Some primary particles are blocky or short-flake shaped, and the contact between adjacent primary particles is relatively close. The overall outline of the secondary particles is relatively complete.
[0047] Figure 1The elemental surface distribution results show that the signals of Na, Mn, O, Cu, and Ti all cover the observed particle region. No obvious micron-scale Cu-rich or Ti-rich regions were observed within the spatial resolution range of the EDS test, indicating that these elements did not undergo severe macroscopic segregation. Because... Figure 1 The surface distribution of Li is not shown, therefore the micro-region distribution of Li is not determined based on this figure, nor is the lattice occupancy state of each element determined separately based on the EDS surface distribution results.
[0048] The phase composition of the obtained NLCTM cathode material was analyzed using X-ray diffraction. Figure 2 As shown, the main diffraction peaks of Example 1 exhibit the diffraction characteristics of P2-type layered oxides, indicating that the obtained material has a P2-phase layered structure. Characteristic diffraction peaks corresponding to a honeycomb superlattice ordered structure were also observed in the range of 2θ from 20° to 40°, indicating that the obtained material formed a superlattice ordered structure while maintaining the P2-phase layered main structure.
[0049] Example 2
[0050] This embodiment prepares a chemical formula of Na. 0.67 Li 0.15 Cu 0.15 Ti 0.05 Mn 0.65 A lithium-copper-titanium co-doped P2-type layered oxide cathode material with O2 was used to investigate the effect of reducing Li content on the material structure and electrochemical performance while keeping Cu and Ti contents constant.
[0051] With a total amount of Li, Cu, Ti, and Mn of 0.02000 mol, the target amounts of Li, Cu, Ti, and Mn are 0.00300 mol, 0.00300 mol, 0.00100 mol, and 0.01300 mol, respectively. Sodium and lithium source compounds are added in 5% excess of their corresponding stoichiometric amounts.
[0052] 1.9146 g of sodium acetate trihydrate, 0.2078 g of lithium acetate, 0.7248 g of copper nitrate trihydrate, 0.07987 g of titanium dioxide, and 3.1861 g of manganese acetate tetrahydrate were weighed out. The operating conditions for raw material dispersion, complexation mixing, water bath gelation, drying, ball milling, pre-calcination, high-temperature calcination, furnace cooling, grinding, and sieving were the same as in Example 1.
[0053] like Figure 2 As shown, the main diffraction peaks of the obtained material exhibit the diffraction characteristics of P2-type layered oxides. Relatively low-intensity superlattice characteristic diffraction peaks can be observed in the range of 2θ from 20° to 40°, indicating that the material obtained in this embodiment possesses a P2-phase layered structure and a weakly ordered superlattice structure.
[0054] Example 3
[0055] This embodiment prepares a chemical formula of Na. 0.67 Li 0.25 Cu 0.15 Ti 0.05 Mn 0.55 A lithium-copper-titanium co-doped P2-type layered oxide cathode material with O2 was used to investigate the effect of increasing the Li content on the material structure and electrochemical performance while keeping the Cu and Ti contents constant.
[0056] With a total amount of Li, Cu, Ti, and Mn of 0.02000 mol, the target amounts of Li, Cu, Ti, and Mn are 0.00500 mol, 0.00300 mol, 0.00100 mol, and 0.01100 mol, respectively. Sodium and lithium source compounds are added in 5% excess of their corresponding stoichiometric amounts.
[0057] 1.9146 g of sodium acetate trihydrate, 0.3464 g of lithium acetate, 0.7248 g of copper nitrate trihydrate, 0.07987 g of titanium dioxide, and 2.6959 g of manganese acetate tetrahydrate were weighed out. All other preparation conditions were the same as in Example 1.
[0058] like Figure 2 As shown, the main diffraction peaks of the obtained material exhibit the diffraction characteristics of P2-type layered oxides, and characteristic diffraction peaks corresponding to the honeycomb superlattice ordered structure appear in the range of 2θ from 20° to 40°.
[0059] The target chemical compositions of Examples 1-3 are shown in Table 2.
[0060] Table 2 Target chemical composition of Examples 1-3
[0061] Comparative Example 1 This comparative example prepares a chemical formula of Na. 0.67 The undoped P2-type layered oxide cathode material of MnO2 is denoted as NM cathode material.
[0062] With Mn amounting to 0.02000 mol and Na amounting to 0.01340 mol, the sodium source compound was added in excess at a 5% stoichiometric ratio. 1.9146 g of sodium acetate trihydrate and 4.9017 g of manganese acetate tetrahydrate were weighed out.
[0063] Both raw materials were ultrasonically dispersed in 100 mL of deionized water for 10 min. Separately, 6.5 g of citric acid monohydrate was dissolved in 50 mL of deionized water, and the raw material mixture was slowly added to the citric acid solution under continuous stirring. The resulting mixture was heated and stirred in an 85°C water bath for 5.5 h to form a gel, and then dried at 120°C for 12 h.
[0064] A zirconia ball mill jar and 5mm diameter zirconia grinding balls were used, and the mixture was ball-milled at 350 rpm for 3 hours at a ball-to-powder mass ratio of 10:1. The resulting powder was placed in a muffle furnace and heated to 580℃ at 3℃ / min under air atmosphere and held for 2 hours, followed by heating to 900℃ at 5℃ / min and holding for 14 hours. The product was cooled in the furnace, ground, and sieved through a 250-mesh sieve to obtain the NM cathode material.
[0065] Comparative Example 2 This comparative example prepares a chemical formula of Na. 0.67 Li 0.20 Mn 0.80 O2-doped Li-doped P2-type layered oxide cathode material.
[0066] 1.9146 g of sodium acetate trihydrate, 0.2771 g of lithium acetate, and 3.9214 g of manganese acetate tetrahydrate were weighed out. Except for the raw material composition, the conditions for raw material dispersion, complexation, drying, ball milling, pre-calcination, high-temperature calcination, and post-treatment were the same as in Example 1.
[0067] Comparative Example 3 This comparative example prepares a chemical formula of Na. 0.67 Cu 0.15 Mn 0.85 O2-doped Cu-type P2-type layered oxide cathode material.
[0068] 1.9146 g of sodium acetate trihydrate, 0.7248 g of copper nitrate trihydrate, and 4.1665 g of manganese acetate tetrahydrate were weighed out. Except for the composition of the raw materials, the preparation conditions were the same as in Example 1.
[0069] Comparative Example 4 This comparative example prepares a chemical formula of Na. 0.67 Ti 0.05 Mn 0.95 Ti-doped P2-type layered oxide cathode material with O2.
[0070] 1.9146 g of sodium acetate trihydrate, 0.07987 g of titanium dioxide, and 4.6566 g of manganese acetate tetrahydrate were weighed out. Except for the composition of the raw materials, the preparation conditions were the same as in Example 1.
[0071] Take the positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-4 respectively, mix the corresponding positive electrode materials, conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1, add N-methylpyrrolidone and stir thoroughly to obtain a uniform positive electrode slurry.
[0072] The positive electrode slurry was uniformly coated onto the surface of a clean aluminum foil and dried at 120°C to remove N-methylpyrrolidone. The dried coated aluminum foil was then cut into circular positive electrode sheets with a diameter of 14 mm. The resulting sodium-ion battery positive electrode comprises an aluminum foil positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector. The positive electrode active material layer contains a corresponding positive electrode material, conductive carbon black, and polyvinylidene fluoride.
[0073] A sodium metal sheet was used as the counter electrode, GF / D glass fiber as the separator, and a 1 mol / L NaClO4 EC / DEC mixed solution as the electrolyte, with a volume ratio of EC to DEC of 1:1. CR2032 button cells were assembled in an argon glove box with water and oxygen contents both below 1 ppm, and their electrochemical performance was tested within a voltage range of 2.0–4.5 V.
[0074] like Figure 2 As shown, the main diffraction peaks of the cathode materials obtained in Examples 1-3 and Comparative Examples 1-4 all exhibit the diffraction characteristics of P2-type layered oxides, indicating that the corresponding materials have formed a P2-phase layered main structure. Examples 1 and 3 show relatively obvious honeycomb-like superlattice ordered structure diffraction peaks in the range of 2θ from 20° to 40°, while the superlattice characteristic diffraction peaks of Example 2 are relatively weak in the same angle range, indicating that the ratio of Li to Mn affects the degree of obviousness of the superlattice ordered characteristics.
[0075] like Figure 3 As shown, Examples 1 and Comparative Examples 2-4 were tested sequentially at 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 5C, 10C, and 20C, and then returned to 1C after the 20C test. Example 1 exhibited approximately 190 mAh·g at 0.1C. ¹ The discharge specific capacity gradually decreases with increasing rate, but remains at approximately 75 mAh·g at 20C. ¹ The discharge specific capacity; after recovery to 1C, its discharge specific capacity recovers to approximately 155 mAh·g. ¹.
[0076] Comparative Examples 2-4 all exhibited some reversible capacity at low magnification, but their overall capacity at high magnification and after recovery to 1C was lower than that of Example 1. Under the same gelation, ball milling, and calcination conditions, the main difference between Example 1 and the three single-element doped samples was the compositional relationship of Li, Cu, Ti, and Mn. Test results showed that the Li used in Example 1... 0.20 Cu 0.15 Ti 0.05 Mn 0.60 The ratio can simultaneously maintain a high low-rate capacity, a good high-rate capacity, and a strong rate recovery capability.
[0077] like Figure 4 As shown, Examples 1-3 used the same Cu content, Ti content, and preparation conditions, only changing the stoichiometric relationship between Li and Mn. Therefore, they can be used to analyze the effect of changes in Li content on the rate performance of the lithium copper titanium co-doped system.
[0078] Example 1 maintains a high discharge specific capacity throughout the various rate stages from 0.1C to 20C, and also has the highest capacity after recovering to 1C; Example 2 has a lower capacity than Example 1 but higher capacity than Example 3 at most rates; Example 3 has a high reversible capacity at low rates, but its capacity decreases significantly as the rate increases.
[0079] Therefore, it can be seen that, with the stoichiometric numbers of Cu and Ti remaining at 0.15 and 0.05 respectively, increasing the stoichiometric number of Li from 0.15 to 0.20 is beneficial to improving the overall rate performance; when the stoichiometric number of Li is further increased to 0.25, the high-rate capacity does not continue to improve. The Li used in Example 1... 0.20 Cu 0.15 Ti 0.05 Mn 0.60 The ratio achieved a good balance of capacity, rate capability, and recovery performance among the three components tested.
[0080] Combination Figure 2 and Figure 4 It can be seen that although Example 3 has relatively obvious superlattice characteristic diffraction peaks, its high-magnification performance is still lower than that of Example 1. This indicates that the overall electrochemical performance of the material is not only determined by the degree of obviousness of the superlattice characteristic peaks, but also corresponds to the proportional relationship between Li, Cu, Ti, and Mn. Example 1 simultaneously possesses the characteristics of a P2 phase layered main structure, a honeycomb superlattice ordered structure, and good overall high-magnification performance. Therefore, Na... 0.67 Li 0.20 Cu 0.15 Ti 0.05 Mn 0.60 O2 is the preferred component.
[0081] like Figure 5 As shown, under a voltage range of 2.0–4.5V and a 1C rate, the initial discharge specific capacity of Example 1 is approximately 150 mAh·g. ¹, after 100 cycles, it still retains approximately 130 mAh·g ¹ The discharge specific capacity of Example 1 is close to 100% overall during cycling. Comparative Example 1 has a lower initial discharge specific capacity, which continuously decays with cycling. These results demonstrate that Example 1 exhibits both high initial capacity and good cycle capacity retention at 1C rate.
[0082] like Figure 6 As shown, under a voltage range of 2.0–4.5V and a 5C rate, the initial discharge specific capacity of Example 1 is approximately 120 mAh·g. ¹, after 300 cycles, it still retains approximately 100 mAh·g The discharge specific capacity of Example 1 was 1; the discharge specific capacity of Comparative Example 1 decreased continuously with cycling and dropped to a low level in the later stages of cycling. Example 1 exhibited a slower capacity decay under high-rate long-cycle conditions.
[0083] like Figure 7 As shown, the apparent Na⁺ diffusion behavior of Example 1 and Comparative Example 1 during charge-discharge processes was compared using a constant-current intermittent titration method. The apparent Na⁺ diffusion coefficients of both materials changed with the state of charge, showing a significant decrease near a specific state of charge. Throughout most of the charge-discharge range, the apparent Na⁺ diffusion coefficient of Example 1 was approximately 0.5 to 1 order of magnitude higher than that of Comparative Example 1; after the diffusion coefficient decreased, Example 1 was able to recover to a relatively high apparent Na⁺ diffusion level. This result corresponds to the fact that Example 1 maintained a high reversible capacity under high-rate conditions.
[0084] like Figure 8 As shown, as the rate gradually increases from 0.1C to 20C, the charge and discharge capacities of both Example 1 and Comparative Example 1 decrease, and the voltage gap between the charging and discharging curves gradually increases. Compared with Comparative Example 1, Example 1 maintains a higher capacity range at different rates, and the capacity shrinkage and voltage polarization under high rate conditions are relatively small.
[0085] comprehensive Figures 1 to 8 Na 0.67 Li 0.20 Cu 0.15 Ti 0.05 Mn 0.60 The O2 cathode material exhibits a layered P2 phase host structure and a honeycomb superlattice ordered structure. No significant micron-scale segregation of Na, Mn, O, Cu, and Ti was observed during EDS analysis. This material demonstrates excellent rate performance, 1C cycling performance, 5C long-term cycling performance, and Na… Both showed good overall results in terms of apparent diffusion behavior.
[0086] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
[0087] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A lithium copper-titanium co-doped P2-type layered oxide cathode material, characterized in that, The general chemical formula of the cathode material is Na. x Li a Cu b Ti c Mn (1 a b c) O2, wherein 0.1≤a≤0.3, 0.1≤b≤0.2, 0.03≤c≤0.08, and a+b+c≤0.4; a, b, c and 1-abc represent the stoichiometric coefficients of Li, Cu, Ti and Mn respectively, and x represents the stoichiometric coefficient of Na; the cathode material has a P2 phase layered structure and a superlattice structure.
2. The lithium copper-titanium co-doped P2-type layered oxide cathode material according to claim 1, characterized in that, The superlattice structure is a honeycomb-shaped superlattice ordered structure, and the X-ray diffraction pattern of the cathode material has the characteristic diffraction peaks of the honeycomb-shaped superlattice ordered structure in the range of 2θ of 20° to 40°.
3. The lithium copper-titanium co-doped P2-type layered oxide cathode material according to claim 1, characterized in that, x=0.67, a=0.20, b=0.15, c=0.05, and the chemical formula of the cathode material is Na. 0.67 Li 0.20 Cu 0.15 Ti 0.05 Mn 0.60 O2.
4. A method for preparing the lithium copper-titanium co-doped P2-type layered oxide cathode material according to any one of claims 1 to 3, characterized in that, The preparation method is sol-gel, and includes the following steps: Step 1: Weigh out sodium source compound, lithium source compound, copper source compound, titanium source compound and manganese source compound according to the feeding ratio corresponding to the chemical formula of the target cathode material. Add the sodium source compound, lithium source compound, copper source compound, titanium source compound and manganese source compound to deionized water and ultrasonically disperse for 10 min to obtain the raw material dispersion system. Step 2: Dissolve the complexing agent in deionized water to obtain a complexing agent solution. Slowly add the raw material dispersion system obtained in Step 1 to the complexing agent solution and continue stirring to obtain a mixed system. Step 3: Heat and stir the mixture obtained in Step 2 in a water bath at 80-90°C for 5-6 hours to obtain a gel. Place the gel in a drying oven and dry it at 120°C for 12 hours to obtain a dry solid. Step 4: Add the dried solid obtained in Step 3 to a ball mill jar for ball milling. The ball-to-material mass ratio is 10:1, the ball milling speed is 200-400 rpm, and the ball milling time is 2-4 hours to obtain dried powder. Step 5: Place the dried powder obtained in Step 4 into a muffle furnace and perform pre-calcination and high-temperature calcination in air atmosphere. The high-temperature calcination is carried out at a heating rate of 2-5℃ / min to 850-950℃ and held for 12-16 hours. After calcination, the powder is cooled to room temperature in the furnace and then ground and sieved to obtain the cathode material.
5. The method for preparing a lithium copper-titanium co-doped P2-type layered oxide cathode material according to claim 4, characterized in that, The sodium source compound is one or more of sodium citrate and sodium acetate; the lithium source compound is one or more of lithium acetate and lithium nitrate; the copper source compound is one or more of copper nitrate and copper acetate; the titanium source compound is one or more of titanium dioxide and tetrabutyl titanate; and the manganese source compound is one or more of manganese acetate and manganese nitrate.
6. The method for preparing a lithium copper-titanium co-doped P2-type layered oxide cathode material according to claim 4, characterized in that, In step one, the amount of sodium source compound and lithium source compound fed in is 5% to 10% in excess of the stoichiometric amount corresponding to the chemical formula of the target cathode material.
7. The method for preparing a lithium copper-titanium co-doped P2-type layered oxide cathode material according to claim 4, characterized in that, In step two, the complexing agent is citric acid or oxalic acid.
8. The method for preparing a lithium copper-titanium co-doped P2-type layered oxide cathode material according to claim 4, characterized in that, In step four, the grinding jar is a zirconia grinding jar, and the grinding balls used are zirconia balls; in step five, the sieving uses a 200-300 mesh sieve.
9. The method for preparing a lithium copper-titanium co-doped P2-type layered oxide cathode material according to claim 4, characterized in that, Step four uses zirconia grinding balls with a diameter of 5 mm, a ball milling speed of 350 rpm, and a ball milling time of 3 h; in step five, the pre-calcination is heated to 580 °C at a heating rate of 3 °C / min and held for 2 h, and the high-temperature calcination is heated to 900 °C at a heating rate of 5 °C / min and held for 14 h.
10. A sodium-ion battery positive electrode, characterized in that, It includes a positive current collector and a positive active material layer disposed on the positive current collector, wherein the positive active material layer comprises the lithium copper titanium co-doped P2 type layered oxide positive electrode material as described in any one of claims 1 to 3.